Increased growth of Araucaria angustifolia under warm conditions is unaccompanied by increased photosynthetic performance - de Castro, Lorena Egidio [UNESP]; Kissmann, Camila [UNESP]; Habermann, Gustavo [UNESP] (Springer Nature, 2017)
Key message: AlthoughA. angustifoliaoccurs in regions with subtropical climate, warm conditions do not seem to impair the growth of young plants. Abstract: The effects of increasing temperature are worth studying even in tree species from subtropical climates. Araucaria angustifolia occurs in the south and southeast of Brazil and in Argentina and its growth and success may be associated with low temperatures. We measured growth, photosynthetic parameters and the nutritional status of this plant growing under artificial warm and cool conditions. We expected growth and photosynthetic performance to increase under cool rather than warm conditions. Under high daily temperature, plants showed increased leaf area per plant, more leaves, containing more nitrogen. However, CO2 assimilation rates at light saturation were similar in plants grown under both conditions, and photosynthetic nitrogen use efficiency was 25% higher in plants under cool conditions. This may be the first report of temperature effects on the growth of this species. Despite enhancing growth in A. angustifolia, warm conditions do not directly influence photosynthetic activities, but enhance leaf area per plant allowing increased CO2 uptake.
Keywords: Brazilian pine; Ecophysiological responses; Gas exchange; Temperature